The Influence of Product Visualization and Customer Reviews on Purchasing Decisions: Muslim Fashion on TikTok Shop Indonesia - Fikriyah, Khusnul; Alam, Wira Yudha (Al-Intaj : Jurnal Ekonomi dan Perbankan Syariah, 2025)
Purpose: The phenomenon of online shopping is becoming increasingly popular today. Clear product information accompanied by attractive photos and videos is a strategy to increase sales. This study aims to determine how product visualization and customer reviews influence purchasing decisions for Muslim fashion products on the TikTok Shop application in Indonesia.Design/methodology: The type of research used is quantitative research with an associative approach. The data collection method is by using a questionnaire aimed at respondents who shop online through the TikTok Shop application. The data collected is processed using SmartPLS.Findings: The results of the study show that product visualization and customer reviews have a significant effect on purchasing decisions. The findings indicate that most respondents read customer reviews before making a purchase to ensure that the Muslim fashion products match the displayed visualization.Practical implications: Businesses in the Muslim fashion industry on TikTok Shop can leverage high-quality product visualizations, including engaging photos and videos, to attract potential buyers and build trust. Companies should prioritize customer testimonials. They need to encourage satisfied customers to leave detailed reviews, ratings, and visual content, such as unboxing videos or photos, to strengthen credibility and influence potential buyers' decisions.Originality/Value: This study focuses on TikTok Shop, a new platform that combines social media and e-commerce. This study provides unique insights into consumer behavior that has not been widely studied before. In addition, this study also integrates cultural and religious aspects that are relevant in Indonesia as the largest Muslim market in the world.